Democracia ex-machina: considerações para a normatização dos bots políticos pelo MERCOSUL, a partir da Teoria do Direito de Thomas Vesting - Lampert, Guilherme Peroni (Universidade do Vale do Rio dos Sinos, 2022)
This work deals with the regulation of political bots by MERCOSUL and proposes to answer how Thomas Vesting's Theory of Law and the respective methodological theory can conceptually indicate the path that MERCOSUL should or can follow to regulate the impact of political bots on the bloc's democratic commitment. The hypothesis of the work was that it would be possible to develop a conceptual model of regulation of the digital public sphere by MERCOSUL, to reduce complexity and promote effective and coordinated measures to combat the dissemination of disinformation by political bots. The research observed the pragmatic-systemic epistemological matrix, applying the systemic approach method and auxiliary methods of descriptive and comparative normative procedure. Conducted a qualitative analysis on the use of bots to influence democratic processes and how the European Union disciplined the issue. It is an eminently theoretical research, whose main research techniques are the bibliographic review and the analysis of the normative acts of the European Union and MERCOSUL. The general objective is to develop a proposal for a regulatory model for political bots for MERCOSUL, based on the Methodological Theory of Vesting. The result of the research confirmed the hypothesis of the work that, based on Thomas Vesting's Theory of Law, MERCOSUR can and must adopt a model of (co)regulation model capable of, from heteroreference to common knowledge, reducing complexity of society and at the same time allow the changes in the environment to lead to the evolution of the legal system and the possibility of justice to come. Furthermore, research has shown that the legal system is indeed sympoietic.
Keywords: Teoria do direito; Teoria dos sistemas; Desconstrução; Cultura digital; Bots; Direito da integração; MERCOSUL; Theory of law; Systems theory; Deconstruction; Digital culture; Integration law; ACCNPQ::Ciências Sociais Aplicadas::Direito